Human rights in Iranian juridical approach - Najafinejad, Alireza; Ahmad, Zaid; Jawan, Jayum (Canadian Academy of Oriental and Occidental Culture, 2010)
There have been different and sometimes conflicting viewpoints regarding Human Rights in Iran from the years after the revolution so far. New and enlightening views have been publicized regarding the relation between Human Rights, Islam, Iran, and the Constitution in recent years including fundamentalists, religious modernists and secular modernists. They have different interpretations on Human Rights based on their positions. This article explains their opinions and differences in interpreting relation between religion and human rights.